2010
DOI: 10.1186/1471-2458-10-442
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards pandemic influenza among cases, close contacts, and healthcare workers in tropical Singapore: a cross-sectional survey

Abstract: BackgroundEffective influenza pandemic management requires understanding of the factors influencing behavioral changes. We aim to determine the differences in knowledge, attitudes and practices in various different cohorts and explore the pertinent factors that influenced behavior in tropical Singapore.MethodsWe performed a cross-sectional knowledge, attitudes and practices survey in the Singapore military from mid-August to early-October 2009, among 3054 personnel in four exposure groups - laboratory-confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
104
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 19 publications
(33 reference statements)
15
104
6
2
Order By: Relevance
“…In the United States, larger household size was a predictor of intended adherence to antiviral medication for the treatment of pandemic influenza, whereas in the Netherlands, intention to take antivirals as prophylaxis was associated with not having children in the household . Other predictors of intended adherence to antivirals included higher risk perception of catching pandemic influenza, knowledge of pandemic influenza and its associated risks and perceived personal consequences of influenza as well as amount of information received about pandemic influenza, increased attention to information and information seeking behaviours . In the United States, trust in the government was also associated with acceptance of antivirals for oneself and one's children .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the United States, larger household size was a predictor of intended adherence to antiviral medication for the treatment of pandemic influenza, whereas in the Netherlands, intention to take antivirals as prophylaxis was associated with not having children in the household . Other predictors of intended adherence to antivirals included higher risk perception of catching pandemic influenza, knowledge of pandemic influenza and its associated risks and perceived personal consequences of influenza as well as amount of information received about pandemic influenza, increased attention to information and information seeking behaviours . In the United States, trust in the government was also associated with acceptance of antivirals for oneself and one's children .…”
Section: Resultsmentioning
confidence: 98%
“…Six additional articles were identified through other search engines such as ScienceDirect and in review articles on the topic area. For one of our included studies, additional information was obtained from the author (Phern‐Chern, personal communication).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several theories such as the theory of planned behavior (Ajzen, 1991) and the health belief model (Rosenstock, 1974), which relied on the knowledge-attitude-practice sequence, have also highlighted the role of knowledge as a precursor to the formation of attitudes and practices. Although studies that applied the knowledge-attitude-practice sequence have shown that attitudes tend to mediate the influence of knowledge on behaviors (e.g., Sessa, Giuseppe, Albano, & Angelillo, 2011;Wang et al, 2010), empirical evidence have also demonstrated that knowledge can have a direct (albeit small) effect on health behaviors (Chew et al, 2002;Morgan & Miller, 2002;Viswanath, 2006;Yap, Lee, Yau, Ng, & Tor, 2010). For example, Yap and colleagues (2010) demonstrated that knowledge has a significant influence on attitudes and behavioral changes among Singaporeans during the H1N1 pandemic.…”
Section: Extensions To Behavioral Intentionsmentioning
confidence: 94%